While Prosopanche (Hydnoraceae) flowers gently heat: mutualistic pollination relationships among the perianth-bearing Piperales - Rocamundi, N.; Miller, M.A.; Maubecin, C.C.; Martel, C.; Moré, M.; Marvaldi, A.; Cocucci, A.A. (Oxford University Press, 2024)
Abstract Flowers of most Piperales do not reward pollinators. However, a few mutualistic pollination relationships have been proposed among the perianth-bearing species. To test the hypothesis of a mutualistic relationship between Prosopanche and beetle pollinators, we studied the pollination biology of three species (P. americana, P. bonacinae, P. panguanensis). For all three species, we recorded flower visitors and flower volatile organic compounds (VOCSs). In addition, for P. americana we investigated flower phases, thermogenesis, visitors’ behaviour, and viability of transported pollen. Using a behavioural experiment, we identified the role of flower heat and fragrance in pollinator attraction. We recorded Neopocadius nitiduloides and Lasiodactylus sp. sap beetles (Nitidulidae) as main pollinators and Hydnorobius hydnorae and H. helleri weevils (Belidae) as occasional pollinators. Thermogenic female flowers heat up to 8°C above the ambient temperature. Flowers only trap the small-sized sap beetles. Methyl-3-methyl-2-butenoate dominated the VOC profile. This was a powerful attractant for sap beetles in controlled bioassays. We conclude that pollination in Prosopanche is mutualistic. This was observed through a pollinator-size-based access limit to the stigmatic chamber and a strong olfactory attractant. Mutualism in Prosopanche therefore contrasts with that of most perianth-bearing Piperales, suggesting it is a novel pollination relationship in early-diverging angiosperms.
Keywords: Perianth; Pollinator; Biology; Pollination; Mutualism (biology); Attraction; Botany; Pollen; Stamen; https://purl.org/pe-repo/ocde/ford#1.05.08